ACPA-positive primary Sjögren's syndrome: true primary or rheumatoid arthritis-associated Sjögren's syndrome?. Issue 1 (30th April 2015) - Payet, J; Belkhir, R; Gottenberg, J E; Bergé, E; Desmoulins, F; Meyer, O; Mariette, X; Seror, R
Abstract : Objectives: Anticyclic citrullinated protein antibodies (ACPA) are highly specific of rheumatoid arthritis (RA). However, they have also been detected in 5–10% of primary Sjögren's syndrome (pSS). We compared ACPA-positive and negative patients with pSS and assessed the risk of evolution to RA. Patients and methods: ACPA-positive and negative patients with pSS were included in this study. For ACPA-positive patients, clinical and radiological re-evaluation was systematically performed after at least 5 years of follow-up. Diagnosis was reassessed at the end of the follow-up to identify patients that developed RA according to the American College of Rheumatology 1987 classification criteria. Results: At inclusion in the cohort 16 patients with pSS were ACPA positive and 278 were ACPA negative. ACPA-positive patients, had more frequently arthritis (43.7% vs 12.2%; p=0.003) but not arthralgias. They also had more frequent lung involvement (25% vs 8.1%; p=0.05). After median follow-up of 8 (5–10) years, 7/16 (43.8%) patients developed RA including 5 (31.25%) with typical RA erosions. Elevation of acute phase reactants at inclusion was the only parameter associated with progression to erosive RA. Conclusions: Median term follow-up of ACPA-positive patients with pSS showed that almost half of them developed RA, particularly in the presence of elevation of acute phase reactants. These results support the usefulness of a close radiological monitoring of these patients for early detection of erosive change not to delay initiation of effective treatment. Indeed, number of these patients with ACPA-positive pSS may actually have RA and associated SS.